Exploring the Utilization of Big Data Analytics in Optimizing Communication Technology Within the Digital Msme Ecosystem in Makassar - Dj, Arini Izzatan Nur; Sultan, Moehammad Iqbal; Amir, Andi Subhan (SENTRI: Jurnal Riset Ilmiah, 2026)
Micro, Small, and Medium Enterprises (MSMEs) are a crucial sector in the Indonesian economy due to their significant contribution to Gross Domestic Product (GDP) and employment absorption. In an increasingly competitive digital era, MSMEs are required to adapt by utilizing data-driven communication technologies to enhance business competitiveness. One relevant approach is Big Data Analytics (BDA), which enables business actors to process large volumes of data to support decision-making and communication strategies. However, the adoption of big data among digital MSMEs remains limited and uneven. This study aims to explore digital MSMEs’ understanding of the big data concept, examine the forms of its utilization in communication practices, and identify the challenges encountered in its implementation in Makassar. The research employed an exploratory qualitative approach with a case study design. Data were collected through semi-structured interviews, participatory observation, documentation, and focus group discussions, and subsequently analyzed using thematic analysis techniques. The findings indicate that most digital MSMEs have a limited understanding of big data and tend to utilize data in relatively simple ways, particularly for basic digital marketing activities. he most significant barrier to big data adoption is not solely technical or financial constraints, but also the low level of strategic urgency among MSME actors in recognizing big data as a critical resource for long-term business development. Key challenges include limited human resources, financial constraints, and inadequate technological infrastructure. Nevertheless, several MSMEs have begun to experience positive benefits from data utilization, especially in supporting digital communication and improving overall business performance.